SISTEM WORLWIDE INTEROPERABILITY FOR MICROWAVE ACCESS PADA SISI KONEKSI NLOS DAN LOS - Susanzepi Susanzepi; Irawan Hadi; Ciksadan Ciksadan (Politeknik Sekayu, 2018)
Wimax provide wireless broadband and mobile terminal in a large geographical area. Wimax 2012 version is providing data rate up to 40Mbit/s and the 2011 version which support speed data up to 1Gbit/s. For stable station, Wimax system use OFDM on Physical layer. Therefore we need an innovative effort to set up layer system that can help the development of telecommunication sector in the future. The superiority of this research is to help the development of telecommunication sector extensively, it is including the Wimax network. Standard wimax have 2 versions : IEEE 802.16-2004 and IEEE 802.16d. this comprehension also supported by Orthogonal Frequency Division ultiplexing on Physical Layer. OFDm provide wireless DSL technology where broadband cable is not available. Wimax 802.16e use Standard OFDMA Technic. It provide the support for nomadic and mobility service also known as WiMAX phone. Wimax is a wireless broadband technology that have an improvement on WI - FI and UMTS. This penelitian will analyst the performance from Physical Layer on Worldwide system Interoperability for microwave access, it expected will speed up the network connection, with the calculate the conditions such as Bit error rate, Digital modulation differential such as BPSK, QPSK, 16QAM and 64QAM can be overcome. In order to achieve low spatial correlation, cross-polarization arrangement between adjacent elements in proposed MIMO antenna is investigated to minimize coupling level. Numerical investigation has been conducted.